Pengaruh Persepsi Iklan, Kesadaran Merek, Citra Merek terhadap Sikap pada Merek dan Keputusan Pembelian (Studi pada Produk Pestisida Merek Sidamethrin 50 EC) - Hakim, Rahma Tiara; Susilowati, Christin (Universitas Brawijaya, Indonesia, 2013)
The purpose of this study is to examine the effect of advertising perception, brand awareness and brand image on brand attitude and its impact on purchase decision. The sample consits of 170 farmer use Sidamethrin 50 E. The method of analysis was the path analysis. The results shows that advertising perception and brand image have positive and significant influence on brand attitude. Advertising perception has a positive and significant toward purchase decision, but brand image not significant toward purchase decision.